2018
DOI: 10.5588/ijtld.17.0521
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of usage and preferences of users for tuberculosis-related text messages and voice calls in Uganda

Abstract: Most urban household TB contacts and rural clinic attendees reported having access to a mobile phone and willingness to receive TB-related personal-health communications by voice call or SMS. However, frequent phone sharing and variable messaging abilities and preferences suggest a need to tailor the design and monitoring of mHealth interventions to target recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…Second, we applied innovative techniques to determine message receipt using SMS reply messages, although uptake of this method of message verification was extremely low. Finally, our study population included young residents of a crowded urban area with high rates of access to mobile phones [21], making our findings likely generalizable to many urban settings in sub-Saharan Africa where health-related SMS interventions are being evaluated and implemented.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, we applied innovative techniques to determine message receipt using SMS reply messages, although uptake of this method of message verification was extremely low. Finally, our study population included young residents of a crowded urban area with high rates of access to mobile phones [21], making our findings likely generalizable to many urban settings in sub-Saharan Africa where health-related SMS interventions are being evaluated and implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Including quizzes or trivia may also improve participant response rates [31]. These strategies, along with more personalized SMS content [21], may increase participant engagement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the widespread adoption of wireless technologies, such as mobile phones in sub-Saharan Africa (76% ownership in 2015; [12]), these technologies can provide accessible and potentially affordable means of providing social support. In a recent study carried out in central Uganda, 75% of TB patients reported owning mobile phones and being willing to receive TBrelated communication via their phones [13]. Mobile phones are thus a promising alternative approach for providing social support to TB patients.…”
Section: Introductionmentioning
confidence: 99%